Edukasi gizi dan pengukuran status gizi (LILA) pada remaja putri sebagai upaya deteksi dini risiko kekurangan energi kronis - A. Fatimah Jamir; Ayu Irawati; Arifah Usman; Wati Wati (JOURNAL of Public Health Concerns, 2026)
Background: Adolescence is a period of rapid growth and development characterized by increased requirements for energy, protein, vitamins, and minerals. Chronic Energy Deficiency (CED) among adolescent girls is a nutritional issue requiring early detection, as it can impact growth, health, academic concentration, and future reproductive readiness. Purpose: To provide knowledge regarding healthy eating patterns and balanced nutrition, and to detect CED risk early through Mid-Upper Arm Circumference (MUAC) measurements among adolescents in a school setting. Method: This community service activity was conducted on June 7, 2026, at SMA Makassar Mulia. The activity employed participatory, promotive, preventive, and empowerment approaches, involving the school in nutritional status monitoring and peer education. Fifteen adolescent girls participated as respondents, with the school facilitating the process. Respondent knowledge and understanding were assessed using a one-group pretest-posttest design, utilizing questionnaires administered before (pretest) and after (posttest) the educational session. Evaluation involved analyzing the aggregated questionnaire results and descriptively reporting on achievements and improvements in respondents' knowledge regarding balanced nutrition and MUAC measurement as a means of early CED risk detection. Results: The activity proceeded successfully and received a positive response from participants and the school. Demographic data showed that the majority of respondents (60.0%) were 17 years old. MUAC measurements revealed that 8 respondents (53.3%) were at risk of CED, while 7 respondents (46.7%) were not. Regarding knowledge scores, the mean score was 65 points prior to the educational activity and increased to 95 points following the session. Conclusion: Nutritional status screening via mid-upper arm circumference (MUAC) measurement and nutrition education for adolescent girls offers benefits by enabling the early detection of the risk of Chronic Energy Deficiency (CED) and enhancing participants' knowledge regarding balanced nutrition, anemia, healthy eating habits, and the consumption of blood-supplementing tablets. These results indicate that integrating screening with nutrition education is an effective approach to raising awareness and supporting efforts to prevent nutritional issues among adolescent girls. Suggestion: It is recommended that schools through peer empowerment conduct periodic activities such as nutritional status monitoring every three to six months, ongoing nutrition education, and support for participants identified as being at risk of CED, as part of school-based adolescent health programs. Keywords: Adolescent girls; CED; Early detection; Mid-upper arm circumference; Nutrition education Pendahuluan: Masa remaja merupakan periode pertumbuhan dan perkembangan yang berlangsung secara cepat serta ditandai dengan meningkatnya kebutuhan energi, protein, vitamin, dan mineral. Kekurangan energi kronis (KEK) pada remaja putri merupakan masalah gizi yang perlu dideteksi sejak dini karena dapat memengaruhi pertumbuhan, kesehatan, konsentrasi belajar, serta kesiapan reproduksi pada masa mendatang. Tujuan: Untuk memberikan pengetahuan mengenai pola makan sehat, dan gizi seimbang serta mendeteksi risiko KEK sejak dini melalui pengukuran lingkar lengan atas (LILA) pada remaja di lingkungan sekolah. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada tanggal 7 Juni 2026 di SMA Makassar Mulia. Kegiatan dilakukan dengan pendekatan partisipatif, promotif, preventif, dan pemberdayaan yang melibatkan pihak sekolah dalam pemantauan status gizi dan edukasi teman sebaya. Kegiatan diikuti 15 remaja putri untuk menjadi responden dan dimediasi oleh pihak sekolah. Pengukuran tingkat pengetahuan dan pemahaman responden dilakukan dengan pendekatan one group pretest and posttest design menggunakan kuesioner yang diberikan sebelum (pretest) dan sesudah kegiatan edukasi (posttest). Evaluasi kegiatan dilakukan dengan menganalisa hasil akumulasi kuesioner dan disampaikan secara deskriptif terkait pencapaian dan peningkatan pengetahuan responden tentang gizi seimbang dan pengukuran LILA sebagai upaya deteksi dini risiko KEK pada remaja. Hasil:  Kegiatan berlangsung dengan baik serta memperoleh respons positif dari peserta dan pihak sekolah yang menunjukkan bahwa sebagian besar responden berusia 17 tahun yaitu sebesar 60.0%, sedangkan berdasarkan hasil pengukuran LILA mendapatkan sebanyak 8 responden (53.3%) berisiko mengalami KEK dan sebanyak 7 responden (46.7%) tidak berisiko mengalami KEK. Sedangkan rata-rata skor pengetahuan responden sebelum kegiatan edukasi mendapatkan nilai mean 65 poin dan mengalami peningkatan setelah kegiatan edukasi mendapatkan nilai mean 95 poin.   Simpulan: Kegiatan skrining status gizi melalui pengukuran lingkar lengan atas (LILA) dan edukasi gizi pada remaja putri memberikan manfaat dalam mendeteksi secara dini risiko kekurangan energi kronis (KEK) serta meningkatkan pengetahuan peserta mengenai gizi seimbang, anemia, pola makan sehat, dan konsumsi tablet tambah darah. Hasil tersebut menunjukkan bahwa integrasi skrining dan edukasi gizi merupakan pendekatan yang efektif dalam meningkatkan kesadaran serta mendukung upaya pencegahan masalah gizi pada remaja putri. Saran: Diharapkan pihak sekolah melalui pemberdayaan teman sebaya untuk melakukan kegiatan secara berkala melalui pemantauan status gizi setiap tiga hingga enam bulan, edukasi gizi berkelanjutan, serta pendampingan bagi peserta yang teridentifikasi berisiko KEK sebagai bagian kegiatan kesehatan remaja di sekolah.